Photovoltaics in Present Days and Their Coexistence with Power System - Jan Turcek; Matej Hrasko; Juraj Altus (Communications - Scientific letters of the University of Zilina, 2011)
The article deals with the issue of presentation of photovoltaic power and photovoltaic power plants, describes their main features, their advantages and disadvantages, and also deals with the possible massive deployment of these power sources to the power system and their impacts on power system operation.